Preseason changes in markers of lower body fatigue and performance in young professional rugby union players - Roe, G. A. B.; Darrall-Jones, J. D.; Till, K.; Jones, B. (European Journal of Sport Science, 2016)
This study investigated the changes in measures of neuromuscular fatigue and physical performance in young professional rugby union players during a preseason training period. Fourteen young (age: 19.1 ± 1.2 years) professional rugby union players participated in the study. Changes in measures of lower body neuromuscular fatigue (countermovement jump (CMJ) mean power, mean force, flight-time) and physical performance (lower body strength, 40 m sprint velocity) were assessed during an 11-week preseason period using magnitude-based inferences. CMJ mean power was likely to very likely decreased during week 2 (-8.1 ± 5.5% to -12.5 ± 6.8%), and likely to almost certainly decreased from weeks 5 to 11 (-10 ± 4.3% to -14.7 ± 6.9%), while CMJ flight-time demonstrated likely to very likely decreases during weeks 2, and weeks 4-6 (-2.41 ± 1% to -3.3 ± 1.3%), and weeks 9-10 (-1.9 ± 0.9% to -2.2 ± 1.5%). Despite this, possible improvements in lower body strength (5.8 ± 2.7%) and very likely improvements in 40 m velocity (5.5 ± 3.6%) were made. Relationships between changes in CMJ metrics and lower body strength or 40 m sprint velocity were trivial or small (<0.22). Increases in lower body strength and 40 m velocity occurred over the course of an 11-week preseason despite the presence of neuromuscular fatigue (as measured by CMJ). The findings of this study question the usefulness of CMJ for monitoring fatigue in the context of strength and sprint velocity development. Future research is needed to ascertain the consequences of negative changes in CMJ in the context of rugby-specific activities to determine the usefulness of this test as a measure of fatigue in this population.